Subjective aging experiences and negative affectivity: examination of fundamental associations and of underlying pathways - Dutt, Anne J. (2018)
The aging process is characterized as a heterogeneous phenomenon with large inter- and intraindividual differences. This multifaceted character of aging cannot be reduced to objective descriptions of aging, such as chronological age or biological age. Instead, the subjective representation of the aging process needs to be taken into consideration. Subjective aging experiences comprise all aspects of the “awareness, perception, experience, evaluation, interpretation, and identification with one’s own aging process” (Westerhof, Whitbourne, & Freeman, 2012, p. 52). Subjective aging research has undergone a boost in the last decades—both with regard to the refinement of its theoretical foundations, as well as with regard to the empirical examination of its plasticity, its antecedents, and its outcomes. In addition, the field has recently witnessed the development of a number of new measurement tools to assess subjective aging experiences. The overarching question of this dissertation asks whether and how subjective aging experiences are linked to psychological well-being. In doing so, major emphasis is put on the negative affectivity–related component of psychological well-being, more specifically depressive symptoms and negative affect/ sad mood. Depressive symptoms and negative affect are examined as antecedents and outcomes of subjective aging experiences. An important research question consists in exploring in which way subjective aging experiences translate into depressive symptoms. Specific research questions, able to differentiate the aforementioned overarching goals, led to four empirical papers gathered in this cumulative dissertation. Paper 1 (see Chapter 2) investigated bidirectional linkages between perceived age-related gains and losses and depressive symptoms in midlife and old age, covering a 2.5-year observational period. Assimilative and accommodative self-regulation strategies and chronological age were studied as moderators. Results suggest that perceived age-related losses in contrast to gains have an effect on change in depressive symptoms over time. This association was stable across the second half of the life span. The reverse effect with depressive symptoms predicting change in perceived age-related losses or gains was not significant. The association between perceived age-related gains and change in depressive symptoms was moderated by self-regulation; when perceived gains were low, less increase in depressive symptoms was reported when accommodation was high. Paper 2 (see Chapter 3) extended these findings by examining the moderating role of two processing strategies, that is, mindfulness and negative repetitive thought, for the association between perceived age-related gains and losses and change in depressive symptoms in middle and old adulthood, covering a 4.5-year observational interval. Mindfulness buffered the harmful effect of high levels of perceived age-related losses on change in depressive symptoms. Conversely, negative repetitive thought exacerbated the detrimental effect of many perceived age-related losses and few perceived age-related gains on change in depressive symptoms. With regard to the interplay between perceived age-related gains and mindfulness, effects were less robust, although the direction of the findings was consistent with theoretical considerations. Effects were comparable across middle-aged and older individuals. Paper 3 (see Chapter 4) focused on the mediating pathways in the association between subjective aging experiences and depressive symptoms. This paper examined the mediating role of future time perspective and general self-efficacy for the association between perceived age-related losses and depressive symptoms in middle and old adulthood based on three measurement points. A higher amount of perceived age-related losses dampened future time perspective and general self-efficacy 2.5 years later, which in turn increased the level of depressive symptoms 2 years later. Effects were comparable across middle-aged and older individuals. Finally, in Paper 4 (see Chapter 5), an experimental mood-induction paradigm was implemented in a sample covering midlife and old age to investigate associations between mood and subjective age. Sad or neutral mood was induced by texts and music. Participants receiving the sad mood induction reported changes toward older felt ages relative to chronological age from pre- to postinduction. Participants receiving the neutral mood induction reported stable levels of subjective age from pre- to postinduction. Effects were comparable across middle-aged and older participants as well as in participants high and low in neuroticism. A conflating discussion of the four individual studies is provided in Chapter 6. The results of this thesis suggest that perceived age-related losses are longitudinally associated with depressive symptoms; that is, perceiving the aging process as being associated with many losses is linked to increasing depressive symptoms. This association is likely unidirectional and not bidirectional. The effect of perceived age-related losses on change in depressive symptoms was moderated by processing strategies (i.e., mindfulness and negative repetitive thought) and mediated by future time perspective and general self-efficacy. Perceived age-related gains were not associated with depressive symptoms at the bivariate level. Considering individual differences, it was found that in case of low levels of accommodation and high levels of negative repetitive thought few perceived gains were linked to increases in depressive symptoms. Regarding short-term associations between subjective aging and well-being, an experimental study suggests that negative affect translates into older felt ages. In conclusion, this dissertation contributes to the understanding of subjective aging experiences in several ways. It suggests that fundamental associations between well-established subjective aging constructs and negative affectivity found in past research can be transferred to a recently developed construct capturing perceived age-related gains and losses. The dissertation illuminates the pathways which explain how subjective aging translates into depressive symptoms (mediators) and suggests that subjective aging always needs to be considered within the context of other individual differences (moderators). The dissertation also provides additional insights into the short-term modifiability of subjective age, taking up the important and so far not well addressed issue of whether subjective age operates at the state- or trait-like level or at both levels. The strong linkages of subjective aging experiences with key developmental outcomes suggest that they should be considered more explicitly and directly within established life-span developmental theories, such as socioemotional selectivity theory (Carstensen, Isaacowitz, & Charles, 1999) or the dual-process model of goal pursuit and goal adjustment (Brandtstädter & Rothermund, 2002). At the practical level, the findings underscore the importance of subjective aging phenomena with regard to psychological well-being. Given the pivotal role of negative views of aging in terms of depressive symptoms and negative affect, our views of the aging process need to be critically reflected. Public health initiatives should more thoroughly consider subjective aging experiences as an integral part in psychological prevention and intervention programs to promote successful aging. The thesis closes with a discussion of ethical concerns tied to the treatment of subjective aging experiences.
Keywords: Hochschulschrift